2015
DOI: 10.2341/14-034-t
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Fragment Reattachment: A Case Report

Abstract: The aim of this article is to present a case report for the multidisciplinary treatment of anterior tooth fractures with invasion of the biologic width and pulpectomy. Successful esthetic and functional results were achieved by bonding the crown fragment, without any form of preparation or the utilization of intracanal posts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…15,16 A study of the literature shows that coronal restoration of teeth with crown-root fractures is usually challenging, especially when the fracture extends below the bone level, as occurred in the present case. 9,13,15,16 One of the determinant factors for the functional and esthetic success in the management of complicated crown-root fractures is the adoption of a multidisciplinary approach involving surgery, endodontics, periodontics, and prosthodontics. 9,13,16,17 The reconstruction of extensively destroyed anterior teeth has become a true challenge for restorative dentistry because dental materials do not effectively substitute for dental tissues.…”
Section: Potential Problemmentioning
confidence: 57%
See 3 more Smart Citations
“…15,16 A study of the literature shows that coronal restoration of teeth with crown-root fractures is usually challenging, especially when the fracture extends below the bone level, as occurred in the present case. 9,13,15,16 One of the determinant factors for the functional and esthetic success in the management of complicated crown-root fractures is the adoption of a multidisciplinary approach involving surgery, endodontics, periodontics, and prosthodontics. 9,13,16,17 The reconstruction of extensively destroyed anterior teeth has become a true challenge for restorative dentistry because dental materials do not effectively substitute for dental tissues.…”
Section: Potential Problemmentioning
confidence: 57%
“…dental remnant, and the patient's age. [13][14][15] The choice of clinicians regarding the restorative treatment of fractured teeth directly affects the treatment prognosis and requires a careful consideration of several factors, such as the extent and pattern of the fracture, the endodontic and periodontal involvement, and the possibility of using the fragment in the reattachment process. 15,16 A study of the literature shows that coronal restoration of teeth with crown-root fractures is usually challenging, especially when the fracture extends below the bone level, as occurred in the present case.…”
Section: Potential Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Amir et al 24 showed that when endodontic therapy is required, the space provided by pulp chamber might be used as an inner reinforcement, thus avoiding any excess preparation of teeth. CMC Taguchi et al 25 reported a case on tooth fragment reattachment by using dual cure resin cement. In this case, the patient was recalled at regular intervals and healing was monitored both clinically and radiographically.…”
Section: Discussionmentioning
confidence: 99%